Identification of Glucogenic Amino Acids Content in Gliricidia maculata as an Alternative Energy Source for High-Yielding Periparturient Dairy Cows - Sulvia Dwi Astuti SW; Budi Prasetyo Widyobroto; Ali Agus; Lies Mira Yusiati (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
Gliricidia maculata which has long been used as a forage for animal feed may contain a variety of glucogenic amino acids variants. The objective of this study was to identify the glucogenic amino acids content in Gliricidia maculata as an alternative source of energy for high-yielding periparturient dairy cows. The samples were the edible portion of plants, harvested randomly at the optimal cutting age (80 days), from the feed plant collection garden of The Faculty of Animal Science, Universitas Gadjah Mada. Lyophilization was carried out by drying the samples at 55°C for 3 x 24 hours continouesly in a Sanyo Drying Oven MOV-112. Pulverization was done by the Foss Tecator CyclotecTM 1093 Sample Mill with 300 mesh (1 mm screen). The hydrolysis of amino acid was carried out using HCl solution while amino acid derivatization used O-phtalaldehyde (OPA) solution. Separation, determination, and quantification of amino acid were carried out by an analytical method in gradient elution using the Thermo ScientificTM DionexTM UltiMateTM 3000 UHPLC Systems with Rapid Separation Fluorescence Detector. Result showed there were at least fourteen kinds of amino acids identified from the samples, i.e.: aspartic acid, glutamic acid, serine, histidine, glycine, arginine, alanine, tyrosin, methionine, valine, phenylalanine, isoleucine, leucine and lysine. Gliricidia maculata contains 1349 ppm glucogenic amino acids, 412.7 ppm ketogenic amino acids and 444.7 ppm glucogenic and ketogenic amino acids. Moreover, there were three types of glucogenic amino acids with the highest concentration were serine (288.7 ppm), glutamic acid (245.5 ppm) and phenylalanine (197.1 ppm) respectively. Glucogenic amino acids can be used as an energy source for dairy cows through gluconeogenesis. This study suggests that Gliricidia maculata may use to supply the precursors of energy for high-yielding periparturient dairy cows to prevent ketosis.